THE CORPORATE CRIMINAL LIABILITY IN THE MANAGEMENT OF OIL PALM PLANTATION LAND - Nur Afita; Hartiwiningsih Hartiwiningsih (UNISSULA, 2022)
This study aims to analyze the form of criminal liability against corporations in the management of oil palm plantation land, especially in West Kalimantan province. Therefore, the corporation as an entity in its development is capable of committing acts against the law such as in the management of oil palm plantations. However, the actual form of criminal liability often contains anomalies in it, especially in the Province of West Kalimantan. This research is empirical legal research or a prescriptive sociological legal research using a statutory approach, and case approach. Analyze what are the obstacles in delegating criminal responsibility to corporations in the field of oil palm plantation land management. The results study show that the form of criminal liability against corporations in the management of oil palm plantations is a criminal fine that can be represented by a senior officer in court. Second, obstacles in delegating responsibility to corporations are caused by several factors, namely (1) the formulation (2) the application (3) the execution.